Q-switched laser generation using MoWS2-rGO in Erbium-doped fiber laser cavity - Ahmad, Harith; Ooi, Shok Ing; Tiu, Zian Cheak; Rahman, B.M. Azizur (Elsevier, 2018)
A saturable absorber (SA) consisting of a Mo (1−x) W x S 2 -rGO composite is proposed and fabricated, and its performance demonstrated. The fabricated Mo (1−x) W x S 2 -rGO has an x composition of 0.2 and is incorporated into a polymer composite thin film. Nonlinear optical characterization of the SA reveals that the Mo (1−x) W x S 2 -rGO/PVA thin film exhibits a relatively high modulation depth of ∼5.9% and low saturation intensity of 0.003 MW/cm 2 . The Mo (1−x) W x S 2 -rGO/PVA thin film SA has an improved optical absorption as well as enhanced photo response, allowing it to generate tunable Q-switched outputs over a range of 56 nm from 1518 nm to 1574 nm in Erbium-doped fiber laser systems. At the optimum lasing wavelength of ∼1560 nm, the highest pulse repetition rate, narrowest pulse width, highest output power and highest pulse energy is achieved at 64.82 kHz, 1.47 μs, 0.37 mW and 5.98 nJ, respectively. The proposed laser would have significant applications in biomedical imaging, material processing environmental sensing and range finding.